Transformasi UKM MOM Menuju Usaha Berkrlanjutan: Integrasi Teknologi Tepat Guna, Pemasaran Digital dan Literasi Manajemen - Soehardjoepri, Soehardjoepri; Ferrinadewi, Erna; Erma Widiana, Muslichah; Anzip, Arino; Saikhu, Ahmad; Wiryawan, Sanny (Seminar Nasional Manajemen, 2025)
UKM MOM is one of the seafood processing enterprises in Tuban Regency that produces various dried fish-based snacks. In its development, this SME faces several challenges in production, marketing, and management. The production process is still highly dependent on weather and electricity, the packaging method remains manual, and limited financial literacy and human resource management are among the main obstacles. This study aims to identify these issues and formulate solutions through the application of appropriate technology, strengthening of digital marketing strategies, and improvement of managerial systems. The research employed a descriptive case study design with qualitative and quantitative approaches, using direct observation and in-depth interviews. The findings indicate that interventions such as the use of oven dryers, generators, digital scales, and water installation improvements significantly enhance production efficiency and continuity. In terms of marketing, the adoption of social media platforms and brand development support has positively impacted market expansion and consumer trust. Meanwhile, in the management aspect, financial recording training and human resource capacity building foster greater professionalism and business sustainability. Overall, the technological and managerial interventions not only serve as short-term solutions but also as strategic steps toward the modernization of community-based enterprises oriented toward efficiency, quality, and sustainable competitiveness.